Logistics support of the Serbian Armed Forces (supply and maintenance through public procurement) - Ilić, Milan D. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The work is based on the Rule of the Technical Service, the Law on Public Procurement, as well as on the experience gained in performing the duties of the Chief of Logistics in the Logistics Battalion of the Armed Forces. It contains the concept of Logistics Support and presents a part of the supply and maintenance system through Public Procurement in the Logistics Battalion of the Armed Forces. Methods: The theoretical system of supply and maintenance is very complex and consists of a number of elements, organizational units, as well as certain principles. During the implementation, it is necessary to take into account all the principles and adhere to the rules and instructions. Also important was the help of colleagues from the Armed Forces and other state institutions who are in relevant positions and are important for logistics support. Results: The final result of the work is a presentation of some activities performed by the logistics body in the battalion with a review of procurement under account 4252. In the final part of the paper, the emphasis is placed on the instructions which regulate and define the division of procurement in more detail, as well as on the implementation according to expenditure account 4252 on "ongoing maintenance and repair of equipment". Conclusion: During the preparation of the paper, the biggest difficulty was the change of various rules and laws. Some rules and literature were written in the 1970s, and are still in force. A proposal for further tendencies would be to define new rules and organizations based on the experience of the countries in the region where the system has taken root.